2019
DOI: 10.1371/journal.pone.0214604
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of senescence tumour markers and its implications on survival outcomes of breast cancer patients

Abstract: Breast cancer is a heterogeneous disease displaying different histopathological characteristics, molecular profiling and clinical behavior. This study describes the expression patterns of senescence markers P53, DEC1 and DCR2 and assesses their significance on patient survival as a single or combined marker with P16 or P14 using breast cancer progression series. One thousand and eighty (1080) patients with primary invasive ductal carcinoma, no special type, were recruited through an 11-year retrospective study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…As noted above, BHLHE40 can be expressed in both the nucleus and the cytoplasm, and its functional role in cancer may vary accordingly ( Figure 2B). BHLHE40 is upregulated in breast cancer compared to normal breast tissue [68][69][70][71][72] -and although the data presented do not refer to the localization of BHLHE40, accompanying immunohistochemical staining shows both nuclear as well as cytoplasmic staining in the tumor tissue [68,71,72]. The function of nuclear BHLHE40 was apparent from other studies, where nuclear BHLHE40 was up-regulated in MCF-7 estrogen receptor positive breast cancer cells www.Genes&Cancer.com upon paclitaxel treatment [103], suggesting that nuclear BHLHE40 prevent tumor progression.…”
Section: Differential Effect Of Bhlhe40 In the Nucleus And The Cytoplasmmentioning
confidence: 62%
See 1 more Smart Citation
“…As noted above, BHLHE40 can be expressed in both the nucleus and the cytoplasm, and its functional role in cancer may vary accordingly ( Figure 2B). BHLHE40 is upregulated in breast cancer compared to normal breast tissue [68][69][70][71][72] -and although the data presented do not refer to the localization of BHLHE40, accompanying immunohistochemical staining shows both nuclear as well as cytoplasmic staining in the tumor tissue [68,71,72]. The function of nuclear BHLHE40 was apparent from other studies, where nuclear BHLHE40 was up-regulated in MCF-7 estrogen receptor positive breast cancer cells www.Genes&Cancer.com upon paclitaxel treatment [103], suggesting that nuclear BHLHE40 prevent tumor progression.…”
Section: Differential Effect Of Bhlhe40 In the Nucleus And The Cytoplasmmentioning
confidence: 62%
“…In two studies of about 1200 breast cancer patients each, BHLHE40 was one of multiple markers predicting disease outcome and metastatic risk [69,70]. A fourth study of 1080 patients with primary invasive ductal carcinoma showed that BHLHE40 expression increased from normal to benign to premalignant and plateaued from premalignant to malignant phenotype [71]. Another study of 147 patients with invasive breast ductal carcinomas showed that BHLHE40 expression was elevated in invasive ductal carcinomas and positively correlated with tumor grade (P = 0.023) [72].…”
Section: Cancers Where Bhlhe40 Expression Is Upregulated Breast Cancermentioning
confidence: 99%
“…Senescent cells are more common in the normal tissues of aged individuals, especially in certain tissue types, such as skin and adipose tissue [ 38 , 39 , 40 ]. They are also present in cancer and in premalignant lesions and have been evaluated as prognostic markers [ 41 ]. The detection of senescence is complicated, as many of the molecules involved in senescence signalling are also oncogenes or tumour suppressors that may be up or down regulated as part of the carcinogenic process.…”
Section: Role Of Senescence As a Prognostic Marker For Cancermentioning
confidence: 99%
“…The diagnosis of atypical hyperplasias increases the risk of being subsequently diagnosed with invasive cancer 40 . In hyperplasias, are common the detection of biomarkers of cellular senescence such as short telomeres, expression of the protein p16, and the infiltration of immune cells [41][42][43] . As it progresses to carcinoma, the recovery in the length of the telomeres, telomerase enzyme activity is observed while decreasing the presence of senescent cells 44,45 .…”
Section: The Carcinogenesis Of Epithelial Tissuesmentioning
confidence: 99%